PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS LECTORA INSPIRE DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS X LINTAS MINAT PADA MATA PELAJARAN GEOGRAFI DI SMAN 1 PADANG SAGO - Dahlia Dahlia; Slamet Rianto; Yuherman Yuherman (JAMBURA GEO EDUCATION JOURNAL, 2022)
This study analyzes interactive learning using Lektora Inspire. The 4D research approach developed by Thiagarajan is used: define, design, develop, and distribute. The students of class X cross-interest at SMAN 1 Padang Sago were studied. The construction of interactive learning media based on Lectora Inspire Inspire by media, language, education, and IT lecturers, and the results obtained are 0.737 and are acceptable. The study revealed that this media can be created and the location of the media determined using Microsoft Excel, with a score of 214 with a mean of 4.89 and 98% with â€œVery Goodâ€ information. The practicality test of Lectora Inspire media based on questionnaire data obtained a score of 2,920 with an average of 4.71, 94% with "Very Practical" knowledge